2007
DOI: 10.1111/j.1399-0012.2007.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing change in health‐related quality of life after liver transplantation

Abstract: Health-related quality of life is influenced by the severity and etiology of cirrhosis-patients with Child class C and those with alcoholic or viral cirrhosis have the poorest quality of life. There were no differences observed among the groups after the transplantation, as the patients with the lowest HRQoLs prior to surgery demonstrated greater gains in HRQoL associated with liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 58 publications
6
45
1
Order By: Relevance
“…A study examining the influence of socioeconomic and demographic factors in the quality of life of liver transplant recipients found that patients with higher educational level had significant scores in the SF-36 Physical Functioning domain (20) . Regarding occupation, most (38.7%) of the patients were professionally active, followed by the retired (35.3%), www.ee.usp.br/reeusp Quality of life in liver transplant recipients and the influence of sociodemographic factors corroborating a study in which employees and housewives corresponded to 37.3% (23) . With advancement of the chronic liver disease and its clinical manifestations, many patients are unable to work and need to quit their jobs either for medical reasons or to undergo the disease treatment in a transplant center outside their city.…”
Section: Discussionsupporting
confidence: 58%
“…A study examining the influence of socioeconomic and demographic factors in the quality of life of liver transplant recipients found that patients with higher educational level had significant scores in the SF-36 Physical Functioning domain (20) . Regarding occupation, most (38.7%) of the patients were professionally active, followed by the retired (35.3%), www.ee.usp.br/reeusp Quality of life in liver transplant recipients and the influence of sociodemographic factors corroborating a study in which employees and housewives corresponded to 37.3% (23) . With advancement of the chronic liver disease and its clinical manifestations, many patients are unable to work and need to quit their jobs either for medical reasons or to undergo the disease treatment in a transplant center outside their city.…”
Section: Discussionsupporting
confidence: 58%
“…MELD and CTP classification were not associated with HRQoL either before or after LTx in this study from Catalonia [7]. However, at 6 months after transplantation, patients with CPT class B and C obtained larger gains in HRQoL than patients with CPT A in the studies by Bryan et al [8] and Estraviz et al [9]. However, the patients with the lowest HRQoL scores before surgery showed greater gains in their quality of life associated with LTx [9], and Kugler et al found that liver transplant recipients reported the lowest HRQoL benefit for the majority of the physical and psychosocial SF-36 subscales as compared with kidney, heart, and lung recipients [10].…”
Section: Discussioncontrasting
confidence: 63%
“…However, at 6 months after transplantation, patients with CPT class B and C obtained larger gains in HRQoL than patients with CPT A in the studies by Bryan et al [8] and Estraviz et al [9]. However, the patients with the lowest HRQoL scores before surgery showed greater gains in their quality of life associated with LTx [9], and Kugler et al found that liver transplant recipients reported the lowest HRQoL benefit for the majority of the physical and psychosocial SF-36 subscales as compared with kidney, heart, and lung recipients [10]. An increasing MELD before grafting score was associated with improved physical HRQoL in the first year after LTx, and did not affect mental HRQoL [11].…”
Section: Discussionmentioning
confidence: 95%
“…30, nº 1 (enero) dicts negative post-transplant outcomes (Kelly et al, 2006;Zipfel et al, 2002). On the other hand, even in the posttransplant phase, because these patients do not achieve the well-being levels of the general population (Estraviz et al, 2007;Kousoulas et al, 2008) and mental health impairment predicts worse daily functioning -by means of fatigue- (Van Ginneken et al, 2010) and mortality after transplant (Pérez-San-Gregorio, Martín-Rodríguez, Galán-Rodríguez, & Borda-Más, 2009). Likewise, if the psychological complications at the pre-waiting-list-study phase are identified and treated, future disorders will be prevented in next stages such as at the waiting-list and post-transplant phases.…”
Section: Discussionmentioning
confidence: 99%